Silent Learners’ Voices: Exploring the Silence Behavior in Indonesian EFL Classroom - Nabella Fariza Zafarina (Yayasan Visi Intan Permata, 2022)
Silence in an EFL classroom is inevitable, but it only becomes an issue when it discourages students from participating, speaking out, or taking an active role in the teaching and learning process. This study's goal is to determine the reasons for learners' silent behavior and expectations in the EFL classroom. Employing an explanatory sequential research design, the data are collected through questionnaires from 78 Indonesian senior high school learners and analyzed using a descriptive statistic to identify the silent learners. Moreover, interviews were given in order to elicit personal explanations for why learners choose to remain silent in EFL classes. The result of this study specifically identified five reasons for silence in EFL classrooms. Furthermore, the empirical findings gained by this study can support linguistic practitioners or educators in developing a more acute awareness and a deeper comprehension of learners' silent behavior